1997
DOI: 10.1111/j.1460-9568.1997.tb01459.x
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptual Grouping Criterion of Colinearity is Reflected by Anisotropies of Connections in the Primary Visual Cortex

Abstract: An important step in the processing of visual patterns is the segmentation of the retinal image. Neuronal responses evoked by the contours of individual objects need to be identified and associated for further joint processing. These grouping operations are based on a number of Gestalt criteria. Here we report that connections in the visual cortex of the cat exhibit a highly significant anisotropy, preferentially linking neurons activated by contours that have similar orientation and are aligned colinearly. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
129
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 274 publications
(153 citation statements)
references
References 39 publications
19
129
0
1
Order By: Relevance
“…Several groups have shown that lateral projections tend to connect regions with the same ocular dominance and with similar orientation preferences (Gilbert and Wiesel, 1989;Malach et al, 1993;Weliky et al, 1995;Yoshioka et al, 1996;Bosking et al, 1997). Most recently, it has been shown that these projections also align with retinotopic axes, according to their preferred orientation, in tree shrews and in cats (Bosking et al, 1997;Schmidt et al, 1997). We have extended this last finding to New World monkeys.…”
Section: Discussionsupporting
confidence: 54%
“…Several groups have shown that lateral projections tend to connect regions with the same ocular dominance and with similar orientation preferences (Gilbert and Wiesel, 1989;Malach et al, 1993;Weliky et al, 1995;Yoshioka et al, 1996;Bosking et al, 1997). Most recently, it has been shown that these projections also align with retinotopic axes, according to their preferred orientation, in tree shrews and in cats (Bosking et al, 1997;Schmidt et al, 1997). We have extended this last finding to New World monkeys.…”
Section: Discussionsupporting
confidence: 54%
“…(1985); Callaway and Wiser (1996) Layer 2/3 cells V1 → Layer 2/3 cells V1 D Recurrent connections (grouping) in 2/3. Bosking et al (1997); Schmidt et al (1997); Raizada and Grossberg (2003) Layer 2/3 cells V1 → Layer 2/3 inhibitory interneurons V1 D Avoid outward spreading (bipole) in 2/3. McGuire et al (1991); Raizada and Grossberg (2003) Layer 2/3 inhibitory cells V1 → Layer 2/3 inhibitory interneurons V1 I Normalization of inhibition.…”
Section: 21mentioning
confidence: 99%
“…The HrzCon are spatially organized in a nonrandom way in relation to the retinotopic map in V1 of the tree shrew (Fitzpatrick, 1996;Bosking et al, 1997), the cat (Schmidt et al, 1997), and the squirrel monkey (Sincich and Blasdel, 2001). In these species, labeled axons extend farther along an axis that corresponds to the preferred orientation at the injection site.…”
Section: Introductionmentioning
confidence: 99%